Influence of being videotaped on the prevalence effect during visual search - Miyazaki, Yuki (Frontiers in Psychology, 2015)
Video monitoring modifies the task performance of those who are being monitored. The current study aims to prevent rare target-detection failures during visual search through the use of video monitoring. Targets are sometimes missed when their prevalence during visual search is extremely low (e.g., in airport baggage screenings). Participants performed a visual search in which they were required to discern the presence of a tool in the midst of other objects. The participants were monitored via video cameras as they performed the task in one session (the videotaped condition), and they performed the same task in another session without being monitored (the non-videotaped condition). The results showed that fewer miss errors occurred in the videotaped condition, regardless of target prevalence. It appears that the decrease in misses in the video monitoring condition resulted from a shift in criterion location. Video monitoring is considered useful in inducing accurate scanning. It is possible that the potential for evaluation involved in being observed motivates the participants to perform well and is related to the shift in criterion.